2018
DOI: 10.1111/jcpt.12724
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective, multicenter study of voriconazole trough concentrations and safety in patients with Child-Pugh class C cirrhosis

Abstract: The voriconazole maintenance dose of 100 mg twice daily or 200 mg daily orally or intravenously may be inappropriate in patients with Child-Pugh class C cirrhosis because of the higher voriconazole C and higher incidence of adverse events. Monitoring voriconazole C earlier is extremely important to prevent the occurrence of voriconazole-related adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…17,23,33 The consequences of increased voriconazole absorption and reduced voriconazole metabolism and/or excretion result in increased overall voriconazole plasma concentration which could lead to increased risk of adverse events, especially with repeated administrations. Previous studies 34,35 showed that the recommended dose and halved maintenance dose in patients with Child-Pugh class B and C cirrhosis may be inappropriate. Therefore, lower doses or longer administration intervals should be considered to reduce the risk of toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,23,33 The consequences of increased voriconazole absorption and reduced voriconazole metabolism and/or excretion result in increased overall voriconazole plasma concentration which could lead to increased risk of adverse events, especially with repeated administrations. Previous studies 34,35 showed that the recommended dose and halved maintenance dose in patients with Child-Pugh class B and C cirrhosis may be inappropriate. Therefore, lower doses or longer administration intervals should be considered to reduce the risk of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A therapeutic concentration range between 0.5 mg/L and 5 mg/L has been recommended in the Chinese Practice Guideline for Individualized Medication of voriconazole to improve treatment outcome and minimize the risk of adverse events. Previous studies suggested that voriconazole trough concentration should be monitored routinely at the initiation of therapy to avoid adverse events, because voriconazole‐related adverse events usually occurred in the first week after voriconazole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors conducted another study including solely patients with Child–Pugh Class C cirrhosis [103]. Patients were allocated to two groups, according to the dosage schedule of voriconazole’s maintenance dose.…”
Section: Antifungal Agentsmentioning
confidence: 99%
“…Further analysis revealed that the increasing C min of voriconazole was associated with increasing incidence of AEs, although no statistical significance was found. It was suggested that in patients with Child–Pugh Class C cirrhosis the halved maintenance dose is probably inappropriate, and that lower dosage should be considered in conjunction with early TDM [103].…”
Section: Antifungal Agentsmentioning
confidence: 99%
“…However, there is no recommended voriconazole regimen for patients with Child-pugh C cirrhosis (CP-C). Meanwhile, our previous study demonstrated that the halved dose still leads to a supratherapeutic level in the majority of cirrhotic patients, with a voriconazole C min of 4.02 ± 2.00 mg/L (14, 15).…”
Section: Introductionmentioning
confidence: 97%